The Contribution to the Study of Dentition State of the Brno Population in the 2nd Half of 18th Century and in the 19th Century - L. Vargová; M. Račanská; L. Horáčková (Czech Dental Chamber, 2008)
The aim of the present study is the description of dentition of skeleton remains from former Town cemetery Malá Nová (nowadays Antonínská Street), which was used as burial site in 1785-1883. A total of 1024 teeth were appraised and 3227 dental alveoli were examined. The caries intensity (I-CE) of the permanent dentition was proved to be about 38.3% and the caries frequency (F-CE) reached up to 83.8%. These two values were higher in the women. From the different types of teeth, most of dental caries were found on molars, afterwards degressively on premolars, incisors and canines. The inflammation changes of dental alveoli were found in 12.7% cases, the degenerative productive process manifestations in 8.3%, the value of the enamel hypoplasia was 4.2%, the teeth retention was observed in 33.8% individuals and the hyperodontia in 0.7% of all studied cases. Results of this study showed that the caries rate in the Brno population of 2nd half of 18th century and in the 19th century, was expressively worse than in historically older populations as well as worse than in the current population.